child and television - TAAOUINAT, Ali (Social Sciences Journal)
We have studied a small sample of pupils of different educational levels from primary to secondary, so that we have dealt with 300 pupils in total, and we have dealt with aspects including television, education, the time spent watching programs and the types of dependent channels, the extent to which parents monitor the programs watched, and finally the relationship between educational return and time spent In watching the programs shown and the type of programs followed as well.